Chat agents respond more empathetically by using hearsay experience - Narimatsu, Hiromi; Sugiyama, Hiroaki; Mizukami, Masahiro; Arimoto, Tsunehiro (Frontiers in Robotics and AI, 2023)
As the responses of chat dialogue systems have become more natural, the empathy skill of dialogue systems has become an important new issue. In text-based chat dialogue systems, the definition of empathy is not precise, and how to design the kind of utterance that improves the user’s impression of receiving empathy is not clear, since the main method used is to imitate utterances and dialogues that humans consider empathetic. In this study, we focus on the necessity of grasping an agent as an experienceable Other, which is considered the most important factor when empathy is performed by an agent, and propose an utterance design that directly conveys the fact that the agent can experience and feel empathy through text. Our system has an experience database including the system’s pseudo experience and feelings to show empathetic feelings. Then, the system understands the user’s experiences, and empathizes with the user on the basis of the system’s experience database in line with the dialogue content. As a result of developing and evaluating several systems with different ways of conveying the above rationale, we found that conveying the rationale as a hearsay experience improved the user’s impression of receiving empathy more than conveying it as the system’s own experience. Moreover, an exhaustive evaluation shows that our empathetic utterance design using hearsay experience is effective to improve the user’s impression about the system’s cognitive empathy.